The Suprachiasmatic Nucleus Regulates Anxiety-Like Behavior in Mice - Vadnie, Chelsea A.; Petersen, Kaitlyn A.; Eberhardt, Lauren A.; Hildebrand, Mariah A.; Cerwensky, Allison J.; Zhang, Hui; Burns, Jennifer N.; Becker-Krail, Darius D.; DePoy, Lauren M.; Logan, Ryan W.; McClung, Colleen A. (Frontiers in Neuroscience, 2022)
Individuals suffering from mood and anxiety disorders often show significant disturbances in sleep and circadian rhythms. Animal studies indicate that circadian rhythm disruption can cause increased depressive- and anxiety-like behavior, but the underlying mechanisms are unclear. One potential mechanism to explain how circadian rhythms are contributing to mood and anxiety disorders is through dysregulation of the suprachiasmatic nucleus (SCN) of the hypothalamus, known as the “central pacemaker.” To investigate the role of the SCN in regulating depressive- and anxiety-like behavior in mice, we chronically manipulated the neural activity of the SCN using two optogenetic stimulation paradigms. As expected, chronic stimulation of the SCN late in the active phase (circadian time 21, CT21) resulted in a shortened period and dampened amplitude of homecage activity rhythms. We also repeatedly stimulated the SCN at unpredictable times during the active phase of mice when SCN firing rates are normally low. This resulted in dampened, fragmented, and unstable homecage activity rhythms. In both chronic SCN optogenetic stimulation paradigms, dampened homecage activity rhythms (decreased amplitude) were directly correlated with increased measures of anxiety-like behavior. In contrast, we only observed a correlation between behavioral despair and homecage activity amplitude in mice stimulated at CT21. Surprisingly, the change in period of homecage activity rhythms was not directly associated with anxiety- or depressive-like behavior. Finally, to determine if anxiety-like behavior is affected during a single SCN stimulation session, we acutely stimulated the SCN in the active phase (zeitgeber time 14-16, ZT14-16) during behavioral testing. Unexpectedly this also resulted in increased anxiety-like behavior. Taken together, these results indicate that SCN-mediated dampening of rhythms is directly correlated with increased anxiety-like behavior. This work is an important step in understanding how specific SCN neural activity disruptions affect depressive- and anxiety-related behavior.